Aktivitas Antioksidan, Kandungan Total Fenolik dan Kandungan Total Flavonoid Pada Beberapa Tumbuhan Berkhasiat Obat Di Kalimantan Timur, Indonesia - Nur Maulida Sari; Irawan Wijaya Kusuma; Nur Indriana Fitriah (ULIN: Jurnal Hutan Tropis, 2021)
Antioxidant activity, total phenolic and total flavonoid contents of some traditional medicinal plants grown in East Kalimantan, Indonesia, were investigated. Plant sample are Macaranga gigantea leaf, Ceiba pentandra leaf, Ceiba pentandra bark, Blumea balsamifera leaf and Artocarpus altilis leaf. Natural antioxidants from plant species are considered safe. Therefore, people are now more interest in finding out the treatment through natural remedies. The plant's total phenolic content was determined by the Folin-Ciocalteu method, while total flavonoid content was determined by the Colorimetric assay method. Antioxidant activity was evaluated by DPPH radical scavenging assay. The results showed that plant samples tested contained 22.02 to 214.88 µg of gallic acid equivalents (GAE)/mg extract represented the total phenolic content. The flavonoid content of the samples was in range from 50.00 to 896.67 µg of catechin equivalents (CE)/mg extract. The plant samples displayed ability to inhibit DPPH free radical formation by 59-81% at 50 ppm concentration. These finding suggest that these plants could possess natural antioxidants and give a scientific basis to the traditional uses of the investigated plants.